Uppföljning av system för vägentreprenörer i skogen - Leppälampi, Mats (2014)
Holmen Skog is one of the largest forestry companies in Scandinavia and they depend heavily on a large network of forest roads for production and logistics in connection to their forestry operations. The company recently introduced a new system for planning of road management. The system will also be developed with the intention to facilitate the monitoring of actions performed by road contractors. This report will provide information to support future decisions regarding further development of the system, after its introduction. In addition to a presentation of results from interviews, the report also provides a smaller study of the different subjects associated with roads, process work and process development.